Industrial policy - Coulter, Steve (LSE Fellow in Political Economy of Europe) (Economy, key ideas., 2023)
Focuses on the formulation and application of industrial policy in late capitalist societies, drawing on economic theory and country-specific case studies to assess future possibilities for effective policy implementation.